Illumination invariant face recognition using principal component analysis -an overview - Kaymak, Ça?ri; Sarici, Rüya; Uçar, Ayşegül (My University, 2013)
Illumination variation is a challenge problem at face recognition since a face image varies as illumination changes. In this paper, it is reviewed the illumination variation techniques in the state-of-the-art such as the single scale retinex algorithm, the multi scale retinex algorithm, the gradientfaces based normalization technique, the Tan and Triggs normalization technique, and the single scale weberfaces normalization technique. The face recognition is performed by using Principal Component Analysis (PCA) in MATLAB environment. AR face database is used for evaluating the face recognition algorithm using PCA. The distance classifier called as Squared Euclidean is used. Experimental results are comparatively demonstrated.
20th Annual International Conference on Mechatronics and Machine Vision in Practice, M2VIP 2013 -- 20 September 2013 through 20 September 2013 -- Ankara -- 102276
Keywords: Face recognition; Illumination variation; MATLAB; Principal Component Analysis